Role of Platelet Mitochondria: Life in a Nucleus-Free Zone - Melchinger, Hannah; Jain, Kanika; Tyagi, Tarun; Hwa, John (Frontiers in Cardiovascular Medicine, 2019)
Platelets are abundant, small, anucleate circulating cells, serving many emerging pathophysiological roles beyond hemostasis; including active critical roles in thrombosis, injury response, and immunoregulation. In the absence of genomic DNA transcriptional regulation (no nucleus), platelets require strategic prepackaging of all the needed RNA and organelles from megakaryocytes, to sense stress (e.g. hyperglycemia), to protect themselves from stress (e.g. mitophagy), and to communicate a stress response to other cells (e.g. granule and microparticle release). Distinct from avian thrombocytes that have a nucleus, the absence of a nucleus allows the mammalian platelet to maintain its small size, permits morphological flexibility, and may improve speed and efficiency of protein expression in response to stress. In the absence of a nucleus, platelet lifespan of 7 to 10 days, is largely determined by the mitochondria. The packaging of 5-8 mitochondria is critical in aerobic respiration and yielding metabolic substrates needed for function and survival. Mitochondria damage or dysfunction, as observed with several disease processes, results in greatly attenuated platelet survival and increased risk for thrombovascular events. Here we provide insights into the emerging roles of platelets despite the lack of a nucleus, and the key role played by mitochondria in platelet function and survival both in health and disease.